Atitudes linguísticas de falantes da área rural e da área urbana do Espírito Santo - Benfica, Samine de Almeida (2024)
This research is an investigation into the linguistic attitudes of speakers from Vitória and San ta Leopoldina, municipalities in Espírito Santo, to comprehend some linguistic notions that exist in these places and the value judgment on verbal agreement structures in first and third person plural without the plural ending (nós gosta, eles brinca). Analyzes are presented of the statements made by some speakers from these comunities about their individual speech and about the speech of their own community, and the perception of the use of variant forms of verbal agreement in the first person plural, with and without plural endings. The central objec tive of this investigation is to analyze the differences between the attitudes of members of an urban community, Vitória, and a rural community, Santa Leopoldina, towards language and the awareness of the varied use of linguistic forms in their own community, comparing the results of linguistic production research already carried out in the two locations, which descri bed the patterns of use of number agreement (Benfica, 2016; Foeger, 2014; Naro et al., 2017; Scherre; Naro; Yacovenco, 2018). To this end, the foundation was based on the theoretical assumptions of Variationist Sociolinguistics (Weinreich; Labov; Herzog, 2006 [1968]), and, more specifically, the notions of attitude, identity, consciousness and linguistic prestige (Fer nández, 1998; Labov, 2006 [1966]). Face-to-face interviews were carried out with residents of both communities, with open questions such as “What do you think about your own way of speaking?”, “Do you notice differences between the way of speaking of those who live in the city and those who live in the countryside ?”, “What do you think of this way of saying: 'We like to get together as a family'?”, among others. The analyzes were predominantly qualitative and showed that, in Vitória, speakers exhibit a more normative and less tolerant attitude towards forms considered less prestigious, especially the first-person variant without a plural mark, in addition to associating it with the speech of those who live in the interior or have less education. In Santa Leopoldina, participants revealed recognition of the use of these non plural constructions in their community, in addition to considering them natural, without ne gative validation, which signals a context of hidden prestige (Labov (2006 [1966]). With re gard to to the perception of the variable use of the first person plural, responses from an onli ne questionnaire carried out prior to the interviews were analyzed, and it was found that between the perception of use and the analyzes of production research there are congruences, when observing the directions of proportions of participant’s responses and quantitative re sults, but inconsistencies are also noted, especially between the production, evaluation and perception of the uses of the verb ir in the present and past tense, particularly the stereotypical expression “nós vai”, which is thought more more frequent than production research shows. It is concluded that speakers from the two communities, Vitória and Santa Leopoldina, are awa re of the varied uses of verbal agreement, and that those from the capital express their rejec tion of structures without plurals, while those from the capital express their rejection of struc tures without plurals from the interior express, in general, normality.